Optimization of nutrient dose for growth and yield of Silybum marianum (L.) Gaertn. under peach based agroforestry system - Chophi, Kikavi; Bhardwaj, D.R.; Thakur, C.L.; Bhutia, P.L.; Bhutia, K.G. (Indian Journal of Agroforestry, 2020)
An experimental trial was conducted to standardize optimum dose of inorganic plus organic fertilizers for production of Silybum marianum (Milk thistle) under peach plants and open field condition. Milk thistle crop was grown with five integrated nutrient doses, viz., T1 (Recommended doses of fertilizers), T2 (75% Recommended doses of fertilizers + 25% Vermicompost), T3 (50% Recommended doses of fertilizers + 50% Vermicompost), T4 (25% Recommended doses of fertilizers + 75% Vermicompost) and T5 (100% Vermicompost). Treatment,T3 showed the best results on most of the growth and yield parameters, viz., plant height (142.15cm), number of leaves plant-1 (147.62), number of branches plant-Â 1 (18.99), number of thistles plant-1 (24.78), LAI (4.70), root-shoot ratio (0.09), total biomass production (10.01q ha-1) and seed yield ha -1 (2.01q ha-1). Peach trees had a positive effect on growth and yield performance of S. marianum, which were found healthier and better thriving underneath its canopy than in sole cropping. Irrespective of the planting condition, soil chemical parameters viz., OC (13.92 g kg-1), available N (312.51 kg ha-1), available P (56.69 kg ha-1) and available K (390.99 kg ha-1) also showed higher value under T3 treatment. However, pH (6.95) and EC (0.27 dSm-1) were found maximum in treatments T4 and T1, respectively. Based on the economic analysis, it was found that S. marianum gave more profit under Treatment T1 (recommended doses of NPK) in terms of monetary value (` 5,71,27 ha-1) when intercropped with peach in comparison to other treatment combinations. From the present investigation, it can be concluded that milk thistle crop under peach based agroforestry system can be a viable option both ecologically as well as economically.